AGE-SPECIFIC SURVIVORSHIP AND LIFE-FERTILITY TABLE STUDY OF INVASIVE ALIEN PEST FALL ARMYWORM ON CASTOR - BHARATI N. BHAT; SRINIVASA CHARY. D, SUPRIYA G.B, SRIDEVI. G, UMA MAHESWARI. T (The Journal of Research, PJTSAU, 2023)
A laboratory experiment was carried out to study the demography of fall armyworm (FAW) in castor at Department of Entomology, College of Agriculture, Rajendranagar, Hyderabad, during 2020-21. Daily observations of FAW from neonates to death of adults was recorded where the age specific survivorship showed decrease in population of FAW on castor at transition of each stage representing the stair step survivorship curve. The net reproductive rate was 324.27, mean generation time (Tc) 30.07 and intrinsic rate of increase (rm) 0.1922 indicating the susceptibility of the host plant. Finite rate of increase (or) female offsprings/female/day (ë) 1.556, doubling time (DT) 3.60 days, weekly multiplication rate (WMR) 3.83 times per week and annual rate of increase (ARI) 1.4223 x 1070, indicated that castor is also a suitable host for FAW. The results on per cent contribution of larvae, pupae and adults were 97.48, 1.38 and 0.20, respectively at stable age distribution of S. frugiperda on castor. The life expectancy (ex) was high in early days i.e., 10.32 (days) and decreased gradually with the age. The present results suggested that in the absence of maize, sorghum and other highly preferred crops, castor crop could become a potential host for FAW. Monitoring needs to be strengthened in order to determine the occurrence of FAW in castor and implement management tactics well in advance.